Analisis Strategi Pengembangan Bisnis Syariah Fleet Card RFID di Pertamina Retail - Fatkurrozi, Muhammad; Yuniawan, Ahyar (Jurnal Ilmiah Ekonomi Islam, 2023)
Optimization of transportation costs is considered one of the toughest and most complex problems in the transportation, freight forwarding and logistics sector. Transportation companies agree that half of the expenses incurred related to the company's current activities are fuel costs. fleet card is a means of payment that functions as a medium of payment and controls expenses for the company's fleet. PT. Pertamina Retail is a large company in the gas station retail business in Indonesia. This study aims to analyze the development of the RFID fleet card business at Pertamina Retail. The approach used is the Business Model Canvas (BMC) and SWOT (Strengths, Weaknesses, Opportunities, and Threats). The research method used is primary data obtained through interviews with several informants. The time of the research starts from February – June 2023. The results of this study show that BMC elements in the form of: key partnerships, customer segments, value propositions and revenue streams are the most dominant blocks. While the lowest is the channel. Pertamina Retail's internal fleet card factors are influenced by network, security, efficiency and financial aspects. The results obtained by the SWOT analysis (strengths, weaknesses, opportunities, & threats) of the nine BMC blocks show that the elements that have the highest strength are the Pertamina brand and gas station network, while the top-up payment mechanism ranks lowest. From another direction, the highest opportunity is the key partnership and the highest threat is the customer segment while the lowest threat is key partners.